PENGARUH MODEL AIR (AUDITORY, INTELLECTUALLY AND REPETITION) TERHADAP KETERAMPILAN KOLABORASI DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Andriani Kumala Dewi, Ririn; Fatkhiyani, Kiki; Dwi Rizka Avianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Background of this research is based on several common problems found in mathematics learning, such as low learning outcomes, students' difficulties in understanding concepts, and a lack of student interest in collaborating with classmates. The purpose of this study is to determine the effect of the AIR model on students' collaborative skills and mathematics learning outcomes in elementary schools. This research was conducted at SDN 1 Karangampel Kidul. The research method used was a True Experimental Design with a Pretest-Posttest Control Group Design. This study used 2 sample groups, namely the control class with 32 students and the experimental class with 32 students. The experimental group was a group of students who were given the AIR (Auditory, Intellectually, and Repetition) model treatment, while the control group was a group of students who used the conventional model. The instruments used were test questions and observation sheets which were then carried out on the experimental and control classes. The results of the study based on the results of the Mann Whitney test to determine the effect of the AIR model on collaborative skills showed an Asymp. Sig. (2-tailed) value of 0.003 < 0.05, meaning the hypothesis is accepted, so there is a difference in collaborative skills between students in the experimental class and students in the control class. In the Mann Whitney test analysis of learning outcomes, it can be seen that the Asymp. Sig. (2-tailed) value is 0.000, so the Asymp. Sig. (2-tailed) value is stated < 0.05. So Ha is accepted and H0 is rejected, meaning the hypothesis is accepted, it is concluded that there is a significant difference in mathematics learning outcomes between the experimental class and the control class. Therefore, it can be concluded that there is an influence of the model (Auditory, Intellectually, and Repetition) on the collaborative skills and mathematics learning outcomes of fourth-grade elementary school students.